2003
DOI: 10.1007/s00018-003-3252-z
|View full text |Cite
|
Sign up to set email alerts
|

Urochordates carry multiple genes for goose-type lysozyme and no genes for chicken- or invertebrate-type lysozymes

Abstract: Genome clones and expressed sequence tags (ESTs) from the ascidian Ciona intestinalis and from the larvacean Oikopleura dioica were analysed for the presence of lysozyme-encoding genes. Two genes were found to potentially code for goose-type lysozymes in Oikopleura, while three or possibly more g-type proteins form the lysozyme complement of C. intestinalis, and at least one of these genes from each species is expressed based on EST data. No genes for chicken- or invertebrate-type lysozymes were found in eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 63 publications
0
33
1
Order By: Relevance
“…In some vertebrates such as in human and zebrafish, two g-type lysozyme genes have been reported (Irwin and Gong, 2003;Callewaert and Michiels, 2010), and two genes coding for g-type lysozymes have been identified in genome database of urochordate, the larvacean Oikopleura dioica, and three or more g-type lysozymes in the ascidian Ciona intestinalis with the expression of at least one gene (Nilsen et al, 2003) However, only one gtype lysozyme gene has been reported from bivalve molluscs (Zou et al, 2005;Zhao et al, 2007) despite some efforts in sequencing genomes of scallops (e.g. Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some vertebrates such as in human and zebrafish, two g-type lysozyme genes have been reported (Irwin and Gong, 2003;Callewaert and Michiels, 2010), and two genes coding for g-type lysozymes have been identified in genome database of urochordate, the larvacean Oikopleura dioica, and three or more g-type lysozymes in the ascidian Ciona intestinalis with the expression of at least one gene (Nilsen et al, 2003) However, only one gtype lysozyme gene has been reported from bivalve molluscs (Zou et al, 2005;Zhao et al, 2007) despite some efforts in sequencing genomes of scallops (e.g. Zhang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In a review on lysozymes, Callewaert and Michiels (2010) identified the presence of g-type lysozyme in genome database of amphibian vertebrates. It was initially considered that g-type lysozyme was restricted to vertebrates (Irwin and Gong, 2003), but biologically functional g-type lysozymes have been identified in urochordates (Irwin and Gong, 2003;Nilsen et al, 2003) and in mollusc invertebrates (see Callewaert and Michiels, 2010). It appears likely that molluscs are the only non-chordate animals from which the g-type lysozyme has been reported, and so far only from bivalve molluscs, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, g-type lysozyme has been linked to innate immune defense in bivalves. In the Zhikong scallop Chlamys farreri, specific nucleotide polymorphisms in the promoter region of the g-type [15,19], Monchois et al [12], Nilsen et al [33] and Van Herreweghe et al [18] except those marked with '*', which are from unpublished data from the authors ? Strong inhibition, ± weak inhibition, -no inhibition, n.t.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the current work, the affinity of PliG was determined only against SalG, and it is possible that g-type lysozymes from mammals, birds, invertebrates or even some bacterial lytic transglycosylases with a g-type lysozyme domain [32] will show a higher affinity. In this context, it is noteworthy that we observed inhibition of the g-type lysozymes in extracts of the Urochordate Oikopleura dioica [33] (data not shown). The specific interaction of PliG and SalG was also investigated by affinity chromatography using the inverse configuration as in SPR, i.e.…”
Section: Specificity and Binding Affinity Of Plig For G-type Lysozymementioning
confidence: 93%
“…The g-type lysozyme was initially identified as an antibacterial enzyme in egg whites from the Embden goose (Canfield and McMurry, 1967), but it was later found to exist in the egg whites of several other bird species (Prager et al, 1974). More recently, the g-type lysozyme has been identified in vertebrate species, including mammals (Nakano and Graf, 1991), fish (Mohanty and Sahoo, 2010), urochordates (Nilsen et al, 2003) and molluscs (Zhao et al, 2007;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%